Clinical correlation between Child Pugh’s score and oesophageal varices in upper gastrointestinal endoscopy in cirrhotic patient (Journal of Kathmandu Medical College, 2017)
Background: Bleeding oesophageal varices are a major complication of portal hypertension following liver cirrhosis. Child Pugh’s score has been used as a prognostic tool while managing a patient with liver cirrhosis.Objective: To clinically correlate Child Pugh’s score and oesophageal varices in upper gastrointestinal endoscopy in cirrhotic patient.Methods: This is a prospective descriptive study done from January 2014 to January 2015. Cirrhotic patients who were referred for upper gastrointestinal endoscopy with or without history of upper GI bleeding were included. Patients were categorized according to Child Pugh’s score into A, B, C and correlated with their endoscopic finding of grading of varices.Results: A total of 50 cirrhotic patients underwent upper gastrointestinal endoscopy during one year. Out of which 60% were in Child Pugh’s category A, 30 % in category B and 10 % in category C. Among them 62% had grade I varices, 20% had grade II varices and 18 % had grade III varices. Those who presented with history of hematemesis had higher grades of oesophageal varices in comparison to those without hematemesis.Conclusion: Cirrhotic patients with higher Child Pugh’s score had higher grades of oesophageal varices leading presentation with hematemesis. Hence, routine screening of cirrhotic patient is necessary before the development of varices.